2017
DOI: 10.1136/oemed-2017-104383
|View full text |Cite
|
Sign up to set email alerts
|

Non-occupational exposure to asbestos and risk of pleural mesothelioma: review and meta-analysis

Abstract: PMM risks from non-occupational asbestos exposure are consistent with the fibre-type potency response observed in occupational settings. By relating our findings to knowledge of exposure-response relationships in occupational settings, we can better evaluate PMM risks in communities with ambient asbestos exposures from industrial or other sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 32 publications
2
30
0
2
Order By: Relevance
“…A recent meta‐analysis explored the association between non‐occupational exposure to asbestos and pleural mesothelioma. Eighteen studies in 12 countries comprising 665 cases were included; a significantly increased risk of pleural mesothelioma was reported for both household exposure (odds ratio [OR], 5.4; 95% CI, 2.6‐11.2) and neighborhood exposure (OR, 6.9; 95% CI, 4.2‐11.4).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta‐analysis explored the association between non‐occupational exposure to asbestos and pleural mesothelioma. Eighteen studies in 12 countries comprising 665 cases were included; a significantly increased risk of pleural mesothelioma was reported for both household exposure (odds ratio [OR], 5.4; 95% CI, 2.6‐11.2) and neighborhood exposure (OR, 6.9; 95% CI, 4.2‐11.4).…”
Section: Epidemiologymentioning
confidence: 99%
“…Different strengths of association were observed according to fiber type, with the strongest associations noted when amphibole was present and the weakest when chrysotile was present. Therefore, the types of fibers to which residents are exposed influences mesothelioma rates. Crocidolite and amosite fibers are considered the main cause of mesothelioma among occupationally exposed individuals …”
Section: Epidemiologymentioning
confidence: 99%
“…However, in 2004, Quebec Public Health only reported a total of 10 cases of pleural mesothelioma among women residing in the mining region at time of diagnosis (six with ‘definite’ diagnoses, five with co-exposures to occupational sources (ref 5, p. 26)). Due to uncertainty of sole domestic exposure versus co-exposures, this report does not meet our inclusion criteria 2. Regardless, no statistically elevated risk of pleural mesothelioma was found for the nine women considered domestically exposed (OR=5.1; 95% CI: 0.6 to 44.6), even with the inclusion of women with occupational co-exposures 5.…”
mentioning
confidence: 93%
“…We reviewed the letter submitted by Finkelstein1 regarding our paper evaluating the risk of pleural mesothelioma from non-occupational asbestos exposure 2. Finkelstein indicated that, in addition to two Canadian studies in our analysis,3 4 a third unpublished report was produced in 2004 by Quebec Public Health 5.…”
mentioning
confidence: 99%
“…Marsh and colleagues1 have published a review and meta-analysis of non-occupational exposure to asbestos and the risk of pleural mesothelioma. They confirmed that non-occupational exposures to asbestos fibres are associated with a large increased risk of pleural mesothelioma and reported a fibre-type potency difference for non-occupational exposures.…”
mentioning
confidence: 99%